2002
DOI: 10.1016/s0040-4020(02)00112-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, hydrolysis, biochemical and theoretical evaluation of 1,4-bis(alkoxycarbonyl)azetidin-2-ones as potential elastase inhibitors

Abstract: AbstractÐA series of 1,4-bis(alkoxycarbonyl)azetidin-2-ones, designed as potential suicide-inhibitors of serine proteases, has been synthesized and evaluated against porcine pancreatic elastase (PPE). The most active compound (K i ,10 mM; reversible inhibitor) was equipped with phenethyloxycarbonyl and benzyloxycarbonyl side-chains at positions N1 and C4, respectively, with the (S)-con®guration. 1 H NMR spectroscopic analysis of the reaction mixtures showed that the ester function is preferentially hydrolyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The capacity of several b-lactam antibiotics [46,47] and monocyclic b-lactams [48][49][50][51][52] to inhibit elastase has been previously reported.…”
Section: Biochemical Evaluationmentioning
confidence: 97%
“…The capacity of several b-lactam antibiotics [46,47] and monocyclic b-lactams [48][49][50][51][52] to inhibit elastase has been previously reported.…”
Section: Biochemical Evaluationmentioning
confidence: 97%
“…The structure of these newly synthesized compounds of 7(a-d) were established by IR, 1 H-NMR, 13 C-NMR, mass data and elemental analysis. 1366 (bending vibrations of imidazole ring), 1140 (C-O) and 725 cm -1 (C-Cl).…”
Section: Synthesis Of 3-chloro-4-(1-(morpholinomethyl) Methyl)-1himidmentioning
confidence: 99%
“…The structure of these newly synthesized compounds of 7(e-h) were established by IR, 1 H-NMR, 13 C-NMR, mass data and elemental analysis. 4-(1-((4-methylpiperazin-1-yl) (1-((4-methylpiperazin-1-yl -4-(1-((4-methylpiperazin-1-yl -4-(1-((4-methylpiperazin-1-yl)…”
Section: ) Methyl) -1h-imidazol-4-yl) -1 -(4-substituted Phenyl) Azetmentioning
confidence: 99%
See 1 more Smart Citation
“…Azetidinones are a very important class of compounds possessing a wide range of biological activities such as antimicrobial [4], anti-inflammatory [5], anticonvulsant [6], antibiotic [7], anticancer [8], anti-elastase [9], antiviral [10], antitumor [4], and anti-HCMV [11] activities. Recently, it has been reported that b-lactams have novel biological properties such as acting as cytomegalovirus protease inhibitors [12], thrombin and tryptase inhibitors [13], cholesterol absorption inhibitors [14], human leukocyte elastease (HLE) inhibitors [15], porcine pancreatic elastease (PPE) inhibitors [16], HIV-1 protease [17], and peroxisome proliferator-activated receptors (PPARs) [18]. Besides their biological activities, the importance of b-lactams as synthetic intermediates has been widely recognized in organic synthesis [19] for example in the semi-synthesis of Taxol [20].…”
Section: Introductionmentioning
confidence: 99%